UPAYA MENINGKATKAN HASIL BELAJAR PADA MATERI SPLDV DENGAN MENGGUNAKAN PENDEKATAN DISCOVERY LEARNING SISWA SMK - Dhea Arianti Permatasari; Luvy Sylviana Zanthy; Gida Kadarisma (IKIP Siliwangi, 2023)
The purpose of this study is to improve student learning outcomes on the subject of Two Variable Linear Equation System (SPLDV) Class X SMK-TI Garuda Nusantara majoring in Computer Network Engineering (TKJ). This research uses classroom action research (Classroom Action Research). Classroom Action Research (CAR) is an action research conducted when a group of people (students) are identified with the problem, then the researcher plans ways to solve it. The problem formulated in this research is to improve student learning outcomes on the subject of SPLDV by using the Discovery Learning approach. In this study, one sample class was taken, namely class X TKJ 2 in 1 group consisting of 13 students in the 2021-2022 academic year. The research instrument used consisted of 2 cycles by conducting an initial test before the action (pre-cycle) and giving a final test after the action (post-cycle). The results of this study indicate that the discovery learning approach can improve student learning outcomes of Class X SMK-TI Garuda Nusantara majoring in Computer Network Engineering (TKJ) with an average score of 84.62 %.